Prediction of yuth and adult recidivism among spanish juveniles involved in serious offenses - Cuervo, Keren (2020)
This study analyzes the predictive validity of the Youth Level of Service/Case Management Inventory (YLS/CMI) for youth and adult recidivism in a Spanish juvenile sample. Participants’ age ranged between 14 and 18.09 years old (N = 264) and 82% were boys and all had been sentenced to probation and custody centers. Data on juvenile and young adult recidivism were collected for the sample with mean follow-up periods of 13.74 and 20.19 months, respectively. The area under the curve, Kaplan–Meier and Cox regression survival analyses were each conducted to check for predictive validity. The findings demonstrated that the YLS/CMI is able to predict recidivism in both the juvenile period and the emerging adult period in a different cultural context. Prior Offenses and Education/Employment emerged as significant predictors for youth and young adult recidivism. The entire YLS/CMI is therefore an effective tool for risk classification in a different cultural sample.